2012
DOI: 10.2147/ijn.s36883
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to the treatment of recurrent aphthous stomatitis with bioadhesive gels containing cyclosporine A solid lipid nanoparticles: in vivo/in vitro examinations

Abstract: Aim:To develop a suitable buccal bioadhesive gel formulation containing cyclosporine A solid lipid nanoparticles (CsA SLNs) for the treatment of recurrent aphthous stomatitis. Methods: The suitability of the prepared formulations for buccal application was assessed by means of rheological studies, textural profile analysis, and ex vivo drug-release studies. Plastic flows, typical gel-like spectra, and suitable mechanical properties were obtained from prepared formulations. The retention time was explored in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 46 publications
3
37
0
Order By: Relevance
“…In our study, we evaluated vaginal retention using a new imaging method: Odyssey Infrared Imaging System with MousePOD™ adapter (LI-COR Biosciences). The benefit of this method is that live animals are used and that they are not exposed to radiation like in radio-imaging studies (34). Near-infrared images of rats administered RDye 800RS Carboxylate dye (peak absorption at 786 nm) loaded chitosan gels are shown in Fig.…”
Section: Results Of In Vivo Distribution Studiesmentioning
confidence: 99%
“…In our study, we evaluated vaginal retention using a new imaging method: Odyssey Infrared Imaging System with MousePOD™ adapter (LI-COR Biosciences). The benefit of this method is that live animals are used and that they are not exposed to radiation like in radio-imaging studies (34). Near-infrared images of rats administered RDye 800RS Carboxylate dye (peak absorption at 786 nm) loaded chitosan gels are shown in Fig.…”
Section: Results Of In Vivo Distribution Studiesmentioning
confidence: 99%
“…In study A7, when compared to the control group, the use of Ciclosporin A gel with solid lipid nanoparticles (NLS/CsA-loaded) showed a reduction in the oral wound area and significantly increased the rate of mucosal repair (22) . The increase in healing speed was also analyzed in study A8, in which a nitric oxide nanoparticle (NO-NP) dressing was used.…”
Section: Discussionmentioning
confidence: 99%
“…A smaller wound area was observed in the poly-Ag group than in the untreated groups and in the Staphylococcus group on days four and seven. A7 Karavana et al 2012 (22) A new approach to the treatment of recurrent aphthous stomatitis with bioadhesive gels containing cyclosporine A solid lipid nanoparticles: in vivo/in vitro examinations A gel formulation of Cyclosporine A loaded with solid lipid nanoparticles (NLS/CsA-loaded) was developed and applied in vivo. The observations were made in rabbits, divided into three groups, in which gingival ulcers were made for application and analysis of the product.…”
Section: A6mentioning
confidence: 99%
“…It has been shown that systemic uptake of active substances (e.g., isotretinoin) through skins could be avoided and SLN could increase the accumulative uptake of the active material in the skin (15). SLNs are produced as liquid dispersions and their incorporation into hydrogels or emulsions helps enhance the retention time in the applied area and patient compliance (16,17).Hydrogels are generally formed from carbomers that have the ability to absorb water, get hydrated and swell by neutralization with a base. Carbomers have been mainly used in liquid or semi-solid pharmaceutical formulations in order to modify their flow characteristics (17,18).…”
mentioning
confidence: 99%
“…SLNs are produced as liquid dispersions and their incorporation into hydrogels or emulsions helps enhance the retention time in the applied area and patient compliance (16,17).…”
mentioning
confidence: 99%